2006
DOI: 10.1002/chem.200600027
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of and Effect of Coadsorption on Water Dissociation on an Oxygen Vacancy of the MgO(100) Surface

Abstract: Malen nach Feldern: Das elektrische Feld einer Rastertunnelmikroskopspitze (links) steuert die Diffusion von Wasserstoff an einer Palladiumoberfläche, sodass charakteristische Muster resultieren. Das STM‐Bild (rechts) zeigt einen dreieckigen Bereich mit niedriger Wasserstoffkonzentration, umgeben von weißen Bereichen, die von Wasserstoff unter der Oberfläche herrühren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…The final stage necessary to close the reaction cycle after formation of either methanol or methane is the regeneration of the F + site and removal of the two hydrogen atoms adsorbed to the surface. Previous work has however shown that for an F 0 -centre water desorption would be an endothermic process 27 and is therefore likely to be a significant limiting step, an observation we confirm with the determination that desorption of H 2 O to leave behind the required F + -centre is endothermic by 170 kJ mol À1 . Within both structures F and G, the unpaired electron density is distributed over the surface-layer magnesium atoms in the first nearest-neighbour shell around the filled vacancy.…”
Section: Resultssupporting
confidence: 88%
“…The final stage necessary to close the reaction cycle after formation of either methanol or methane is the regeneration of the F + site and removal of the two hydrogen atoms adsorbed to the surface. Previous work has however shown that for an F 0 -centre water desorption would be an endothermic process 27 and is therefore likely to be a significant limiting step, an observation we confirm with the determination that desorption of H 2 O to leave behind the required F + -centre is endothermic by 170 kJ mol À1 . Within both structures F and G, the unpaired electron density is distributed over the surface-layer magnesium atoms in the first nearest-neighbour shell around the filled vacancy.…”
Section: Resultssupporting
confidence: 88%
“…Calculations were performed using the hybrid quantum mechanical and molecular mechanical (QM/MM) embedded-cluster methodology that has previously proven to be accurate in modelling the bulk and surface chemistry of MgO. 8,[34][35][36][37][38][39][40][41][42][43] Our chosen QM/MM implementation is the software environment ChemShell, [44][45][46] with QM and MM energy evaluations performed with the NWChem 47 and GULP [48][49][50] software packages, respectively, and geometry optimisation was performed using the DL-FIND software routines. 45 For the QM calculations, density functional theory (DFT) was used with the B3LYP [51][52][53] and B97-3 54 exchange-correlation (XC) functionals.…”
Section: Computational Methodologymentioning
confidence: 99%
“…The relationship of anion-cation charge transfer depends on the geometric characteristics and the cation electronegativity of the oxides. 52 Several physical parameters such as cationic and anionic radius and their formal charge, electro negativity and oxygen partial charge play a key role in metal oxides synthesis. It has been also reported that influence of oxygen vacancies on the wettability of water varies of the order of 51% on a hydrated ZnO (100) surface interaction between water as compared to the hydrated ZnO surface.…”
Section: Selection Of Materials-role Of Surface Cation and Oxygen Vmentioning
confidence: 99%
“…Various studies have reported different estimation of the iconicity for compound including alkaline earth oxides, that is, Al 2 O 3 , Fe 2 O 3 , NiO MgO to BaO. The relationship of anion‐cation charge transfer depends on the geometric characteristics and the cation electronegativity of the oxides 52 . Several physical parameters such as cationic and anionic radius and their formal charge, electro negativity and oxygen partial charge play a key role in metal oxides synthesis.…”
Section: Factors Affecting the Performance Of Hecmentioning
confidence: 99%